PENGARUH SOSIAL BUDAYA TERHADAP PERNIKAHAN DI BAWAH UMUR - Muhammad Janky Dawsat (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
ABSTRAC Marriage is generally carried out by adults regardless of profession, religion, ethnicity, poor or rich, living in villages or cities. The age of marriage is too young resulting in an increase in divorce cases due to lack of awareness to be responsible in married life for husband and wife. The phenomenon of underage marriage may occur in various regions. Likewise in Jatibarang District, underage marriage is no longer a strange thing but has become a common thing. more or less gives a perception to the community to marry off their children even though they have not reached the age set by the Law itself. The purpose of this study was to determine the views of the community in Jatibarang Subdistrict, Indramayu Regency on underage marriages, to determine the factors causing underage marriages in Jatibarang Subdistrict, Indramayu District, and to determine the implications of underage marriages in Jatibarang Subdistrict, Indramayu Regency. This research was conducted using qualitative methods or a combination of both in dealing with the sociology of law starting with questions. There are also researchers who have used analytic discourse methods in studying legal texts, or conducted in-depth interviews with judges. The results of this study concluded that the perception of Jatibarang Subdistrict to early marriage was a marriage that was done by someone who was not yet married or mature. Where a woman who has not menstruated or menstruated and a man who has never dreamed of. But it must also be estimated age by looking at his physical condition. Early marriage is agreed upon by the community because it is considered appropriate and is considered an adult if a person has reached the age that is in Marriage Law Number 16 Year 2019.